An eco-sustainable approach towards heavy metals remediation by mangroves from the coastal environment: A critical review. (March 2023) - Yadav, Krishna Kumar; Gupta, Neha; Prasad, Shiv; Malav, Lal Chand; Bhutto, Javed Khan; Ahmad, Akil; Gacem, Amel; Jeon, Byong-Hun; Fallatah, Ahmed M.; Asghar, Basim H.; Cabral-Pinto, Marina M.S.; Awwad, Nasser S.; et al.
Abstract: Mangroves provide various ecosystem services, carbon sequestration, biodiversity depository, and livelihoods. They are most abundant in marine and coastal ecosystems and are threatened by toxic contaminants like heavy metals released from various anthropogenic activities. However, they have significant potential to survive in salt-driven environments and accumulate various pollutants. The adverse effects of heavy metals have been extensively studied and recognized as toxic to mangrove species. This study sheds light on the dynamics of heavy metal levels, their absorption, accumulation and transport in the soil environment in a mangrove ecosystem. The article also focuses on the potential of mangrove species to remove heavy metals from marine and coastal environments. This review concludes that mangroves are potential candidates to clean up contaminated water, soil, and sediments through their phytoremediation ability. The accumulation of toxic heavy metals by mangroves is mainly through roots with limited upward translocation. Therefore, promoting the maintenance of biodiversity and stability in the coastal environment is recommended as an environmentally friendly and potentially cost-effective approach. Graphical abstract: Unlabelled Image Highlights: Mangroves can survive in salt-driven marine (ME) and coastal ecosystems (CE). They are threatened by excessive heavy metals (HMs) levels in their environment. This review discussed the HMs level, their uptake, and transport in mangroves. Mangroves acts as natural remediator of HMs through phytoremediation approach. They mostly accumulate HMs in the roots with limited transfer to the aerial parts.